EMPLOYEE ENGAGEMENT PADA KARYAWAN BACK OFFICE PERUSAHAAN JASA KEPELABUHANAN: PERAN TEAM AND CO-WORKER RELATIONSHIP DAN CAREER DEVELOPMENT - Fardiansyah, Zhulfikar Alief; Nurcholis, Gartinia; Utami, Dessy Nur (Jurnal Psikologi, 2024)
The importance of having employee engagement is when employees are bound to form positive emotional relationships with the company, it will affect employees' attitude toward clients, so it will give benefits to the company because it can improve the services provided and customer satisfaction obtained. This research aims to examine the effect of team and co-worker relationships and career development on employee engagement. Data collection of as many as 84 employees, using an incidental sampling technique. The measuring instruments used are the Utrecht Work Engagement Scale (UWES) which has been modified, the Team and Co-worker Scale, and the Career Development Scale. The results show there are influence between team and co-worker relationships and career development on employee engagement together or partially in back office employees. Team and co-worker relationships are important external factors because mutually supportive interpersonal relationships can lead to high employee engagement. After all, they are built based on harmonious relationships. Likewise, career development is also an important external factor because if employees are provided with adequate development programs, they have the potential to engage by work role and organization. This research can be a recommendation for companies to make strategies to increase employee engagement especially involving team and co-worker relationships and career development factors.